UCP3 gene polymorphism and insulin resistance in obese female adolescents - Dian Eurike; Harry Freitag Luglio Muhammad; Rina Susilowati; Madarina Julia (Indonesian Pediatric Society Publishing House, 2012)
Background A previous study on obese female adolescents in Yogyakarta done in the year 2007 suggests that genetic factors might influence insulin resistance. One genetic factor that has been associated \\lith insulin resistance in other populations is the 􀁐55C;T polymorphism in the uncoupling protein 3 (UCP3) gene. Objective To investigate an association between the 􀁐55C;T polymorphism in the UCP3 gene and insulin resistance in obese female adolescents in Yogyakarta. Methods A total of79 obese female adolescents were enrolled in this cross􀁐sectional study. Genotyping of the 􀁐 5 SC/T polymorphism in the UCP3 gene was performed by polymerase chain reaction􀁐 restriction fragment length polymorphism (PCR􀁐RFLP). Results The TiT homozygous individuals had a higher risk of insulin resistance (OR 2.3; 95% CI 0.4 to 14.1), as well as higher fasting insulin concentration and homeostatic model assessment for insulin resistance (HOMA􀁐IR) compared to individuals v.ith other genotypes. The T allele carriers also had a higher risk of insulin resistance (OR 1.3; 95% CI 0.7 to 2.5), as well as higher fasting insulin concentration and HOMA􀁐 IR compared to C allele carriers. However, none of these results were statistically significant (P > 0.05). Conclusion The TiT genotype and T allele of the UCP3 gene 􀁐55CiT polymorphism was not significantly associated increased risk of insulin resistance in obese female adolescents in Yogyakarta. [Paediatr lndanes. 2012;52:152-6].